Dual Lp-Mixed Geominimal Surface Area and Related Inequalities. (10th July 2016) - Ma, Tongyi; Feng, Yibin
Abstract : The integral formula of dual L p -geominimal surface area is given and the concept of dual L p -geominimal surface area is extended to dual L p -mixed geominimal surface area. Properties for the dual L p -mixed geominimal surface areas are established. Some inequalities, such as analogues of Alexandrov-Fenchel inequalities, Blaschke-Santaló inequalities, and affine isoperimetric inequalities for dual L p -mixed geominimal surface areas, are also obtained.